Workload in throwing dominant sports: an infographic summary - Zaremski, J. L.; Pazik, M.; Duncan, J.; Horodyski, M. B. (British Journal of Sports Medicine, 2023)
Substantial interest in the concept of workload and its applications to training and injury prevention programmes is evident in the literature. The majority of the published data regarding workload surrounds lower extremity-based sports involving running activities such as track and field events as well as soccer. However, there has been an increased interest in the workload concept related to throwing and overhead sports in recent years. In particular, cricket, baseball, softball, volleyball, water polo, handball and lacrosse have been studied.